Aquatic insect diversity as water quality indicator in Pagsipi-Bunggo-Camatian river, Lucban, Quezon - Luciano, Angelo Joshua C.; Salluta, John Claude Renan B. (2016)
The main aim of the study is to determine the water quality of Pagsipi-Bunggo-Camatian River based on the presence of key aquatic insects. It also aims to determine the diversity and eveness of such aquatic insects and correlate the result on various physicochemical parameters the abundance of collected aquatic insects. Three quadrats were established along the river and the sampling was conducted in 6 sampling cycles (Day and Night) using D-frame net, Kick-Seine net, Surber Stream-Bottom Sampler and Ligth trap to catch samples. A total of 987 individuals were obtained belonging to 38 families from the 9 insect orders identified. Results show that the diversity of Pagsipi and Bunggo is high while Camatian is low based on the scores obtained using the two diversity indices. The eveness value of Bunggo is the highest with 0.728, Pagsipi with 0.594 and Camatian with 0.141. Water in Bunggo and Pagsipi are considered clean, but with doubts on its quality, while water from the Camatian is severely polluted.
Keywords: Aquatic insects; Water quality